Effect of antiplatelet agents on Escherichia coli sepsis mechanisms: A review - Mariotti, Antoine; Ezzraimi, Amina Ezzeroug; Camoin-Jau, Laurence (Frontiers in Microbiology, 2022)
Despite ever-increasing improvements in the prognosis of sepsis, this condition remains a frequent cause of hospitalisation and mortality in Western countries. Sepsis exposes the patient to multiple complications, including thrombotic complications, due to the ability of circulating bacteria to activate platelets. One of the bacteria most frequently implicated in sepsis, Escherichia coli, a Gram-negative bacillus, has been described as being capable of inducing platelet activation during sepsis. However, to date, the mechanisms involved in this activation have not been clearly established, due to their multiple characteristics. Many signalling pathways are thought to be involved At the same time, reports on the use of antiplatelet agents in sepsis to reduce platelet activation have been published, with variable results. To date, their use in sepsis remains controversial. The aim of this review is to summarise the currently available knowledge on the mechanisms of platelet activation secondary to Escherichia coli sepsis, as well as to provide an update on the effects of antiplatelet agents in these pathological circumstances.